GAMBARAN PERUBAHAN TEKANAN DARAH SESAAT SETELAH MELAKUKAN SENAM PADA LANSIA HIPERTENSI DI DESA SUNDUL MAGETAN: Description of Changes in Blood Pressure Immediately After Doing Exercise In Hypertension Elderly - Hartono, Aris; Adhin Al Kasanah; Dika Lukitaningtyas (Jurnal Penelitian, 2023)
Hypertension is a sickness that frequently happens in the older. One way to reduce high blood pressure is to do elderly exercise regularly. In some studies blood pressure can increase shortly after physical activity. This study plans to depict changes in circulatory strain in the wake of doing older practice in old individuals with hypertension. This study utilizes an expressive observational plan with a cross sectional methodology. The sample in this study was 30 respondents, namely elderly people who experienced hypertension in Sundul Village, Parang District, Magetan Regency, who took part in elderly gymnastics. The sampling technique uses total sampling. Observation of blood pressure was carried out 30 minutes after doing elderly exercise. The information examination procedure was done spellbindingly. The outcomes showed that the greater part of the respondents' systolic circulatory strain diminished with a typical decline of 12.57 mmHg. The conclusion of the study that elderly exercise can reduce systolic blood pressure.